Концесії – прогресивний інструмент інвестиційного забезпечення розвитку морських портів України - Кудрицька, Н.В. (Економіко-математичне моделювання соціально-економічних систем, 2016)
Considered the problems and major risks application concessions in the ports of Ukraine. Offered the model of the timing transmission port concession depending on the amount of investment on the experience of the port Antwerp.